Femtosecond dynamics of secondary radiation formation from quantum well excitons - Taylor, R; Haacke, S; Deveaud, B; Joseph, I; Zimmermann, R (1998)
The time-resolved secondary emission of resonantly created excitons in GaAs quantum wells is studied using femtosecond up-conversion spectroscopy. The behaviour of the rise and decay of the secondary emission and reflectivity in quantum welts is strongly dependent upon the disorder at the interfaces, the exciton density and the temperature. In the case of low densities and temperatures the emission is independent of the exciton density and rises quadratically in time, in excellent agreement with recent theory for Rayleigh scattering from two-dimensional excitons subjected to disorder. These rise times are compared directly with T-2 times measured by time-integrated four-wave mixing (FWM). The comparison of the dynamics displayed in time-resolved secondary radiation and time-integrated FWM provide a clear understanding of the coherence properties of QW excitons in the first few picoseconds after excitation. High-contrast oscillations that are due to quantum beats between the heavy- and light-hole Is-states are seen. The visibility decay at very low densities is long tau(HL) = 25 ps and is related to the action of potential fluctuations on the scattering of heavy-hole and light-hole excitons. (C) 1998 Elsevier Science B.V. All rights reserved.